Northern hemisphere summer mesospheric gravity wave response to solar activity from nine years of AIM observation. (15th October 2019) - Thurairajah, Brentha; Bailey, Scott M.; Hervig, Mark E.
Abstract: High-latitude northern hemisphere summer mesospheric gravity wave (GW) activity at PMC altitude (82–86 km) is analyzed from nine years (2007–2015) of Aeronomy of Ice in the Mesosphere (AIM) satellite observation. GW activity is characterized in terms of potential energy per unit mass. A new method is proposed to convert the Ice Water Content (IWC) in Polar Mesospheric Cloud (PMC) observed by the Cloud Imaging and Particle Size (CIPS) experiment on the AIM satellite to temperature using a simple model. These are used with temperatures from the Solar Occultation for Ice Experiment (SOFIE, also onboard the AIM), to derive daily averaged GW potential energy in the northern hemisphere summer. July monthly averaged GW potential energy indicates no relation to the 11-year solar cycle. Daily averaged values indicate a large variability in the 27-day GW oscillation, with positive, negative or no correlation with the 27-day solar rotation during individual summer seasons. However, a superposed epoch analysis using SOFIE GW anomalies indicate a significant negative response to the 27-day solar rotation with a lag of 8–12 days. This 27-day GW response may be related to similar oscillations in the wind, but the exact cause of the 27-day signal in the GW activity is not yet understood. Highlights: Summer mesospheric gravity waves are characterized in terms of potential energy. July averaged gravity wave activity indicate no relation to the 11-year solar cycle. Gravity wave anomalies indicate a negative response to the 27-day solar rotation.